2012
DOI: 10.1002/jmri.23539
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐modal quantitative MRI investigation of brain tissue neurodegeneration in multiple sclerosis

Abstract: Purpose To investigate the utility of multimodal quantitative magnetic resonance imaging (qMRI) and atlas-based methods to identify characteristics of lesion-driven injury and neurodegeneration in relapsing remitting multiple sclerosis (RRMS) Materials and Methods This work is health insurance portability and accountability act compliant. High resolution T1-weighted, dual echo and fluid-attenuated inversion recovery and diffusion tensor MRI images were prospectively acquired on 68 RRMS patients (range 25–58 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
1
2

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 62 publications
3
34
1
2
Order By: Relevance
“…Interestingly, in 2004, Law et al demonstrated that the NAWM of patients with relapsing remitting MS (RRMS), shows decreased perfusion compared with that of controls [322] by using dynamic susceptibility contrast material-enhanced perfusion magnetic resonance (MR) imaging. In 2012, Hasan et al employed quantitative DTI in the study of brain tissue neurodegeneration in MS patients [323] with lesion-driven injury and neurodegeneration in relapsing remitting MS (RRMS). Widespread cerebral pathology and a neurodegenerative injury component that was independent from lesions in RRMS were demonstrated.…”
Section: Neurological Diseasementioning
confidence: 99%
“…Interestingly, in 2004, Law et al demonstrated that the NAWM of patients with relapsing remitting MS (RRMS), shows decreased perfusion compared with that of controls [322] by using dynamic susceptibility contrast material-enhanced perfusion magnetic resonance (MR) imaging. In 2012, Hasan et al employed quantitative DTI in the study of brain tissue neurodegeneration in MS patients [323] with lesion-driven injury and neurodegeneration in relapsing remitting MS (RRMS). Widespread cerebral pathology and a neurodegenerative injury component that was independent from lesions in RRMS were demonstrated.…”
Section: Neurological Diseasementioning
confidence: 99%
“…IN DIFFUSION TENSOR imaging (DTI) studies of brain white matter regions‐of‐interest (ROI), manual outlining of ROIs can be particularly time‐consuming and may introduce user bias. Automated selection of white matter ROIs can be accomplished with atlas‐based segmentation . According to this approach an image volume corresponding to a white matter atlas is registered to an individual's image volume, and the resulting spatial transformation is applied to the white matter labels of the atlas to transform them to the individual's space.…”
mentioning
confidence: 99%
“…In addition, dual fast spin-echo (FSE) images were acquired with echo and repetition times of TE1/TE2/TR = 8.2/90/6800 ms and a FLAIR sequence with (TE/TI/TR = 80/2500/8000 ms). These images were used for lesion quantification [19, 20]. The slice thickness for both FSE and FLAIR data was 3.0 mm with 44 contiguous axial slices covering the same inferior-to-superior prescription of the 3D T1-weighted sequence and a square field-of-view (FOV) of 240 mm.…”
Section: Methodsmentioning
confidence: 99%
“…All human brain MRI data sets were masked to remove non-brain tissues and estimate the intracranial volume (ICV) for each subject as described elsewhere [19, 20]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation